giải pt
a)\(\dfrac{1}{x+1}+\dfrac{3}{2x+1}=\dfrac{8}{x-2}\)
b)\(\sqrt{2x+1}+\sqrt{3-x}=\sqrt{3x+5}\)
Giải PT
a) \(4x^2-3\sqrt{3}x-6=0\)
b) \(\left(1-\sqrt{5}\right)x^2-3x+\sqrt{5}+1=0\)
Giải PT:
a) \(4x^2-3\sqrt{3}x-6=0\)
b) \(\left(1-\sqrt{5}\right)x^2-3x+\sqrt{5}+1=0\)
giải pt bằng phương pháp đặt ẩn phụ
\(x^2+\left(3-\sqrt{x^2+2}\right)x=1+2\sqrt{x^2+2}\)
Giải phương trình:
1, \(2\left(x^2-x+1\right)^2+x^3+1=\left(x+1\right)^2\)
2, \(\sqrt{2x+3}+\sqrt{x+1}=3x+2\sqrt{2x^2+5x+3}-16\)
3, \(x^2+\sqrt{x+5}=5\)
giải pt
\(x^2+x=2\sqrt{3}\left(x+1\right)\)
giải pt
\(x^2+2\sqrt{2}x+2\sqrt{2}-1=0\)
Giải phương trình :
\(x^2-2x+3=\sqrt{2x^2-x}+\sqrt{1+3x-3x^2}\)
Giải pt: 2.(1+\(\sqrt{ }\)x2 +x+1)= x.(x+1)